Wearable technology usage among students of the University of Debrecen - Ráthonyi, Gergely; Ráthonyi-Odor, Kinga; Szabados, György; Bács, Zoltán; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2023)
The lack of physical activity and the growing prevalence of a sedentary lifestyle are urgent public health problem worldwide. The problem is also typical of the young population, especially university students, who spend most of the day in a sitting position. Technological development is one of the catalysts for the rise of a sedentary lifestyle, nevertheless, thanks to this, many devices have appeared on the market that can be used to encourage physical activity. The widespread of wearable activity tracker devices – wristwatches, wristbands – among the population shows a constantly increasing trend, with a parallel increase in the amount of data collected about ourselves (step count, calories burned, heart rate). The main goal of the present study derives from the recognition of the gap in this field in the domestic sports science literature therefore our focus is on modern information technology tools in the dimension of physical activity. The aim of this study is to assess the attitudes of the university student population towards activity-tracking devices. We conducted a cross-sectional online quantitative survey (questionnaire) among DE GTK students. 340 people filled out the questionnaire correctly. In addition to descriptive statistics, parametric and non-parametric tests (Pearson’s chi-square test, Fisher’s exact test, t-test, Mann-Whitney test) were used to examine the relationships. The results of the statistical tests were considered significant if p<0.05. We performed the distribution of the variables using the Kolgomorov-Smirnov test. The majority of respondents (55%) have already tried some kind of wearable device that measures physical activity. Every third student (34%) are currently using their device. Those who have not tried these devices so far indicated the price as the primary deterrent. 32% of the students plan to invest in such a device in the future. 39% of device users use an activity tracker bracelet, while 61% use or used a smartwatch. In terms of sex, we did not find any differences in asset ownership. The primary goal of the students (66.8%) was to track their physical activity. The most frequently used function was tracking the number of steps, indicated by 81% of the respondents, followed by heart rate measurement (67%). Most of them (69%) set some kind of goal regarding their number of steps. According to every third student, they moved more as a result of the device and managed to maintain the increased level of physical activity. 44% of the students claimed that their physical activity did not change despite using the device. Students tend to disagree with the positive statements related to the devices in connection with a healthy lifestyle. Although the present study suggests that wearable devices have an impact on students and they track their measured data, it is questionable whether the devices themselves are enough of an incentive for students to develop a healthier lifestyle.